Factors associated with neonatal mortality in the African Great Lakes region: A pooled analysis of national surveys - Blessing Jaka Akombi; Pramesh Raj Ghimire; Andre Masumbuko Renzaho (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Neonatal mortality is a major public health problem and accounts for about one third of the deaths of children under-5 years. The aim of this study was to estimate the rate and predisposing factors associated with neonatal mortality in the African Great Lakes region (Burundi, Congo Democratic Republic, Kenya, Rwanda, Tanzania and Uganda). # Methods The study used cross-sectional data from the most recent Demographic and Health Survey of countries in the African Great Lakes region. A total sample of 56600 neonatal deaths of singleton live-born infants was reported across the region. Neonatal mortality was defined as the death of a newborn within the first 28 days of life. Cox regression model was used to identify factors associated with neonatal mortality in the African Great Lakes region. # Results The Democratic Republic Congo had the highest neonatal mortality rate per 1000 births (19, 95% confidence interval (CI)=17-21) within the region followed by Uganda (18, 95% CI=16-21) and Tanzania (16, 95% CI=14-19). Multilevel logistic regression analysis shows that factors significantly associated with neonatal mortality were: Sex of child (male neonates; hazard ratio (HR)=0.79, 95% CI=0.65-0.96), perceived birth size (small neonates; HR=1.88, 95% CI=1.47-2.39), birth order and birth interval (first child; HR=3.05, 95% CI=2.28-4.07), 4th or more child with \> 2 years birth interval (HR=0.48, 95% CI=0.36-0.66), previous death of baby (HR=10.3, 95% CI=7.75-13.68), non-usage of contraceptives (HR=1.81, 95% CI=1.43-2.29), non-receipt of tetanus toxoid injection (HR=1.36, 95% CI=1.04-1.78), no antenatal care visits (HR=1.62, 95% CI=1.06-2.48), and delivery through caesarean section (HR=1.89, 95% CI=1.40-2.55). # Conclusions To meet the Sustainable Development Goals (SDGs) target for neonatal mortality, interventions should focus on increasing access to good quality healthcare services for women and their newborns as well as family planning services and home-based neonatal care services.